แนวทางการบริหารงานบุคคลตามหลักสาราณียธรรม 6 ของผู้บริหารสถานศึกษา สังกัดองค์การบริหารส่วนจังหวัดร้อยเอ็ด - คำผาลา, ภัทรพล; ถิ่นแสนดี, ธีรภัทร์ (วารสารการบริหารการศึกษา มมร.วิทยาเขตร้อยเอ็ด; Vol 3 No 3 (2566): กันยายน-ธันวาคม 2566, 2023)
บทความวิจัยนี้มีวัตถุประสงค์ 1)เพื่อศึกษาการบริหารงานบุคคลตามหลักสาราณียธรรม 6 ของผู้บริหารสถานศึกษาสังกัดองค์การบริหารส่วนจังหวัดร้อยเอ็ด 2) เพื่อเปรียบเทียบการบริหารงานบุคคลตามหลักสาราณียธรรม 6 ของผู้บริหารสถานศึกษาสังกัดองค์การบริหารส่วนจังหวัดร้อยเอ็ด จำแนกตามเพศ ระดับการศึกษา และประสบการณ์การทำงาน 3) เพื่อศึกษาแนวทางการบริหารงานบุคคลตามหลักสาราณียธรรม 6 สำหรับผู้บริหารสถานศึกษาสังกัดองค์การบริหารส่วนจังหวัดร้อยเอ็ด กลุ่มตัวอย่างได้แก่ ผู้บริหาร และครู จำนวนทั้งสิ้น 92 คน ผู้ให้สัมภาษณ์ 4 ท่าน เครื่องมือที่ใช้ในการวิจัยเป็นแบบสอบถาม และแบบสัมภาษณ์กึ่งโครงสร้าง สถิติที่ใช้ในการวิจัย ได้แก่ ความถี่ ร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน t-test และ F-test (One-Way ANOVA) และการวิเคราะห์เชิงเนื้อหา ผลการวิจัยพบว่า   1) ระดับการบริหารงานบุคคลตามหลักสาราณียธรรม 6 ของผู้บริหารสถานศึกษาสังกัดองค์การบริหารส่วนจังหวัดร้อยเอ็ด โดยรวมอยู่ในระดับมาก เมื่อพิจารณารายด้านโดยเรียงจากด้านที่มีค่าเฉลี่ยสูงสุดไปต่ำสุด  ได้แก่ ด้านการประเมินผลการปฏิบัติงานบุคลากร ด้านการวางแผนกำหนดตำแหน่ง ด้านการบำรุงรักษาบุคลากร   ด้านการสรรหาคัดเลือกบุคลากร   และด้านการพัฒนาบุคลากร ตามลำดับ 2) ผลการเปรียบเทียบระดับความคิดเห็นที่มีต่อการบริหารงานบุคคลตามหลักสาราณียธรรม 6 ของผู้บริหารสถานศึกษาสังกัดองค์การบริหารส่วนจังหวัดร้อยเอ็ด จำแนกตามเพศ และระดับการศึกษาไม่แตกต่างกัน ส่วนจำแนกตามประสบการณ์การทำงาน แตกต่างกันอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 3)  แนวทางการบริหารงานบุคคลตามหลักสาราณียธรรม 6 ของผู้บริหารสถานศึกษาสังกัดองค์การบริหารส่วนจังหวัดร้อยเอ็ด ซึ่งมีแนวทางมีการกำหนดตำแหน่งที่เหมาะสมกับภาระงานต่างๆ มีการสรรหาบุคลากรที่มีความรู้ความสามารถตรงกับความต้องขององค์กร มีการนิเทศและติดตามผลการดำเนินงานพร้อมส่งเสริมให้บุคลากรเข้ารับการพัฒนาและอบรมในด้านต่างๆ ตามความสามารถ มีการกำหนดเป้าหมาย วิสัยทัศน์ นโยบาย เพื่อให้บุคลากรมีเป้าหมายและกำลังใจในการปฏิบัติงาน และมีการประเมินผลงานการปฏิบัติงานบุคลากรทุกคนอย่างเป็นธรรมและโปร่งใส จากบทสัมภาษณ์ของผู้บริหารสถานศึกษา 1)การบริหารงานบุคคลเป็นสิ่งที่ต้องให้สำคัญอันดับแรกในการทำงาน ผู้บริหารควรกำหนดนโยบายโครงสร้างและหน้าที่ของบุคลากรอย่างชัดเจน 2)ผู้บริหารส่งเสริม สนับสนุนให้บุคลากรได้เข้ารับการอบรม เพื่อพัฒนาตนเองและวิชาชีพให้เกิดความก้าวหน้าในวิชาชีพและมีคุณภาพชีวิตที่ดี 3)มีการประเมินผลการปฏิบัติงานของบุคลากรอย่างเป็นธรรม โปร่งใส มีเมตตา ยึดหลักความเท่าเทียมและเสมอภาค The objectives of this research were 1) to study the personnel management based on Saranee Dhamma six for School administrators under Roi Et Provincial Administrative Organization, 2) to compare the personnel administration based on  Saranee Dhamma six of educational institution administrators under Roi Et Provincial Administrative Organization, Roi Et Province, classified by gender, level of education, and work experience 3) to study the guidelines for personnel management based on Saranee Dharma six for school administrators under Roi Et Provincial Administrative Organization. The sample group was 92 administrators and teachers, and 4 interviewees obtained. The research tool was questionnaire and a semi-structured interview. The Statistics used were frequency, percentage, mean, and standard deviation, t-test and F-test (One-Way ANOVA) and content analysis. The research results showed that: 1. The level of personnel administration based on Saranee Dharma six of school administrators under Roi Et Provincial Administrative Organization, overall, was at a high level. When considering each aspect, sorted from the aspect with the highest average to the lowest were personnel performance appraisal, position planning, maintenance personnel, recruitment and selection of personnel and personnel development, respectively. 2. The results of comparing the level of opinion towards personnel administration based on Saranee Dhamma six of school administrators under Roi Et Provincial Administrative Organization, classified by gender and education level were no difference. Once classified by work experience, the difference was statistically significant at the .05 level. Division by work experience, the difference was statistically significant at the .05 level. 3.  Guidelines for Personnel management based on Saranee Dharma 6 for School administrators under Roi Et Provincial Administrative Organization which has a guideline to determine the position that is suitable for various workloads. Recruitment of personnel with knowledge and competence that meets the needs of the organization, supervision and follow-up on performance, along with encouraging personnel to develop and train in various fields according to their ability goals, visions, and policies are set so that personnel have goals and morale in their work. The management must evaluate the performance of all personnel fairly and transparently. From an interview with school administrators 1) Personnel management is the first priority in work. Executives should clearly define policies, structures and duties of personnel. 2) Promotion executives encourage personnel to attend training for developing one's self and profession for professional advancement and good quality of life 3) Employees' performance is evaluated fairly, transparently, with kindness, adhering to the principle of equality and impartiality.